Cassane-type diterpenes from Caesalpinia minax induce apoptosis in pituitary adenoma: structure–activity relationship, ER stress and Wnt/β-catenin pathways. Issue 5 (4th May 2017) - Li, Zong-Yang; Li, Qing-Zhong; Ma, Guo-Xu; Chen, Lei; Zhang, Ce; Chen, Bao-dong; Yang, Jun-Shan; Li, Wei-Ping
Abstract: Plant-derived natural products have been the highly significant sources of novel antitumor agents. The cassane-type diterpenes of genus Caesalpinia have been reported to bear antiproliferative activities toward different types of cancer cells. In this study, we evaluated the antineoplasmic activities of 16 natural origin cassane-type diterpenes isolated from the CHCl3 extract of the seeds of C. minax in pituitary adenomas cells and identified caesalpin G (CAG) showed the strongest cytotoxicity. Moreover, we further investigated the structure–activity relationship and molecular mechanism of these derivatives systematically. The results confirmed the unsaturated lactone-type ring, hydroxyl at C-7, and alkenyl at C-11 or C-14 functionality as critical for anticancer activity in this family of natural products. In addition, the mechanism experiments also demonstrated unfolded protein response and ER stress and Wnt/β-catenin pathway were involved in the CAG-induced apoptosis.